Adherent Invasive Escherichia coli Strains from Patients with Crohn's Disease Survive and Replicate within Macrophages without Inducing Host Cell Death - Glasser, Anne-Lise (American Society for Microbiology, 2001)
Escherichia coli strains recovered from Crohn's disease (CD) lesions are able to adhere to and invade cultured intestinal epithelial cells. We analyzed the behavior within macrophages of adherent invasive E. coli (AIEC) strains isolated from patients with CD. All the 15 AIEC strains tested were able to replicate extensively within J774-A1 cells: the numbers of intracellular bacteria increased 2.2- to 74.2-fold at 48 h over that at 1 h postinfection. By use of murine peritoneal macrophages and human monocyte-derived-macrophages, the reference AIEC strain LF82 was confirmed to be able to survive intracellularly. Transmission electron micrographs of AIEC LF82-infected macrophages showed that at 24 h postinfection, infected cells harbored large vacuoles containing numerous bacteria, as a result of the fusion of several vacuoles occurring after 8 h postinfection. No lactate dehydrogenase (LDH) release, no sign of DNA fragmentation or degradation, and no binding to fluorescein isothlocyanate-labeled annexin V were observed with LF82-infected J774-A1 cells, even after 24 h postinfection. LF82-infected J774-A1 cells secreted 2.7-fold more tumor necrosis factor alpha (TNF-α) than cells stimulated with 1 μg of lipopolysaccharide (LPS)/ml. No release of interleukin-1β was observed with LPS-prestimulated J774-A1 cells infected with AIEC LF82. These findings showed that (i) AIEC strains are able to survive and to replicate within macrophages, (ii) AIEC LF82 replication does not induce any cell death of the infected cells, and (iii) LF82-infected J774-A1 cells release high levels of TNF-α. These properties could be related to some features of CD and particularly to granuloma formation, one of the hallmarks of CD lesions.